Sculpture of Vishnu - 023.JPG - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Vishnu holding Shankha, Chakra, and Padma can be identified in the image. Other artefacts are not clear.